Keabsahaan Pengangkatan Kepala Pemerintahan Negeri Lisabata Timur Kabupaten Maluku Tengah - Tomalima, Ilham Agus; Nendissa, Renny Heronia; Lainsamputty, Natanel (Jurnal Saniri, 2023)
The village government system in Maluku in the customary regime is known as State government and generally applies to Ambon Island and Central Maluku Regency. State government is the basis of indigenous peoples and has clear land and sea territorial boundaries called petuanan country, and a government system that is genealogical or based on lineage. The term Negeri does not come from the native language of this area or "the language of the land". A country is a territorial alliance consisting of several sub-districts, which are generally at least three. Currently, the composition of the government of the territory of the country is the territory that forms the country. Underneath there are soa areas which are formed from several old houses as genealogical alliances.This research method is descriptive, namely to describe, find legal facts as a whole and examine systematically related to the arrangement for the appointment of the head of government of the State of East Lisabata and examine whether the appointment process is in accordance with applicable regulations. The conceptual approach is used to research and search for new legal concepts. Information was collected from various literatures to obtain legal instruments and relative research sources.It is hoped that the results of this research in the future, related to the election mechanism/procedure and the appointment of the East Lisabata State Government Head, can be carried out properly and correctly in accordance with the provisions of the Central Maluku Kanupaten Government Regulation Number 03 of 2006 concerning Procedures for Nomination, Election, and inauguration of the Head of State Government and existing legislation. The East Lisabata Indigenous Peoples Unit also needs to pay attention to rational considerations about the quality of the candidate they choose, both the moral, emotional, social, and intellectual qualities of the Candidate for Head of State Government to be nominated.